The health improvement profile (HIP) : a manual to promote physical wellbeing in people with severe mental illness - Hardy, Sheila (College teacher) (M & K Publishing, 2015)
This practical guide, written by experts in mental health nursing, is designed to support healthcare practitioners in checking the physical health of people with severe mental illness (SMI). As life expectancy is reduced by 12 to 19 years in people with SMI, this patient group should receive a physical health check at least once a year. Yet many mental health practitioners have not been trained to assess their physical health needs, and even when such training is offered it may be difficult to access it because of clinical workloads. The Health Improvement Profile (HIP) provides an efficient, ef.